The science in human science research: The case for Rasch measurement in learning environment research - Cavanagh, Rob; Fisher, W. (2018)
© 2018 Institute of Physics Publishing. All rights reserved. The field of learning environment research has a 40 year history originating in the USA with the work of Herbert Walberg and Rudolf Moos, who utilised Kurt Lewin's Field Theory. The conception of a learning environment employed in learning environment research has social and psychological aspects with a focus on learning, student achievement, and student attitudes. In 1984, the American Educational Research Association (AERA) special interest group (SIG) on the Study of Learning Environments was formed, and in 1998 the first edition of the Learning Environments Research journal (LERj) was published. This paper examines the features of the survey instruments developed to measure aspects of classrooms and other environments where learning occurs. The traditions of Classical Test Theory, True-Score Theory and Rasch's models for unidimensional measurement are related to learning environment research as reported in the LERj. Measurement theories are associated with three philosophical orientations: positivism, anti-positivism, and post-positivism. The paper concludes with some examples of how a measurement science extending Rasch's models can be applied in learning environment research.